Two-terminal molecular memory through reversible switching of quantum interference features in tunneling junctions - Carlotti, Marco; Sauter, Eric; Zharnikov, Michael (Angewandte Chemie. International edition, 2018)
Large-area molecular tunneling junctions comprising self-assembled monolayers of redox-active molecules are described that exhibit two-terminal bias switching. The as-prepared monolayers undergo partial charge transfer to the underlying metal substrate (Au, Pt, or Ag), which converts their cores from a quinoid to a hydroquinoid form. The resulting rearomatization converts the bond topology from a cross-conjugated to a linearly conjugated π system. The cross-conjugated form correlates to the appearance of an interference feature in the transmission spectrum that vanishes for the linearly conjugated form. Owing to the presence of electron-withdrawing nitrile groups, the reduction potential and the interference feature lie close to the work function and Fermi level of the metallic substrate. We exploited the relationship between conjugation patterns and quantum interference to create nonvolatile memory in proto-devices using eutectic Ga-In as the top contact.
First published: 27 September 2018
Gesehen am 29.03.2019